The template-assisted synthesis of polypyrrole hollow microspheres with a double-shelled structure1. Issue 24 (25th March 2015) - Niu, Chunyu; Zou, Bingfang; Wang, Yongqiang; Chen, Lin; Zheng, Haihong; Zhou, Shaomin
<x xml:space="preserve">Abstract</x> Double-shelled polypyrrole hollow microspheres were synthesized via a novel template-assisted concept, using iron oxide hollow microspheres as both the sacrificial template and initiator in acidic solution.